Analysis of time overruns in roads and highways sector in India using AHP ranking technique - K. Pai, Siddesh; Kumar Singh, Avinash; Mittal, Ankur; Anand, Neeraj (International Journal of Engineering and Technology, 2018)
In todayâ€™s scenario there will be a competition exists among various construction firm, so the risk management come into picture to assess the various risk related to project. Assigning the right severity factor as per the possibility of occurrence will impart the success of organization as well as success will impart the growth of nation with increase in G.D.P. In construction of road the assessment of right severity factor, will be considered as strength to lower down the delay of time over run. Tremendous amount of effort are applied in quantitative and qualitative manner for assessment of risk severity factor. However, many criteria for risk severity factor enable the decision making methods will smoothen the process of arriving at a solution and enable decision makers to make the right decisions. Decision-making problems need systematic approach to appraise the various alternatives using quantitative and non quantitative factors. Standard methods for solving problems will lack considerations of non-quantitative factors, where numeric values are difficult to assign. Different techniques like, Analytic Hierarchy Process (AHP), Fuzzy set theory Making and Multi Criteria Decision are being used in risk severity factor. These techniques consider factors with concrete values or vague values. This research will provide solution to a risk severity factor for budget allocation problem, for allocating funds to competing and deserving organizations by using ranking analysis technique. Fuzzy set theory and AHP is used to calculate the Weights .Fuzzy set considers subjective values like preferred, strongly preferred etc. and Analytic Hierarchy Process (AHP) technique evaluates relative importance of factors by making pair wise comparison matrix. The evaluation technique will facilitate in ranking of various severity factors according to their possibility of occurrence after assigning weights to decision making factor.Â Â Â